Q: What is 6 squared plus -3 squared?

Write your answer...

Submit

Related questions

6 squared plus 3 is equal to 39.

6 squared is 36. 36 plus 3 is 39

15.

5x squared plus 33x plus 18 = (5x + 3)(x + 6) x = -6, -3/5

6 squared plus 9 squared is equal to 117.

104

9 - 4 =5, 5+36= 41

3 squared plus 2 squared is equal to 13.

That factors to (2c + 3)(3c + 2)

(5x + 2)(x + 3)

(x + 3)(x + 2)

It is 36/6 +4 = 10

It is: 36 plus 121 = 157

40

3 - 3 squared = 6 * * * * * NO! 3 - 3 squared = 3 - 9 = -6

2(x + 3)(x + 1)

285

p2 + 9p + 18/ p + 6(p + 6)(p + 3)/ p + 6(p + 6)(p + 3)/ p + 6p + 3

2 squared plus 2 x 3 = 10, 7 squared plus 7 x 2 = 63, 6 squared plus 6 x 5 = 66,8 squared plus 8 x 4 = 96 so 9 squared plus 9 x 7 = 81 + 63 = 144.

100 is.

(x + 3)(x + 2)

(-4,-6)

73

X squared = x+6 6+x=x squared X=6

Asuming it starts "x squared" the the answer is (x-3)(x-3) or (x - 3)squared